Literature Review of the Application of DEA Methodology in the Colombian Educational Field - Arcadio Cervera Muñoz; Wilson Oviedo García; Julia Andrea Pineda Acero (Civilizar, 2013)
This article presents the results of a literature review in the national intellectual production, related to the application of the methodology of Data Envelopment Analysis (DEA, for its acronym in English) in the Colombian education. Specifically, and as of this review, the article establishes the characteristics of the objects of study of the researches and presents how the methodology is used. In conclusion, although DEA management has been increased, it is still in its infancy and therefore, there are several research opportunities that include different types of decision units (DMU), types of institutions, educational levels, coverage and study objectives.